MENINGKATKAN MINAT BELAJAR IPS DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE SCRAMBEL UNTUK SISWA KELAS VIII A SMP NEGERI 3 BELAWANG - Annie Annie (JURNAL SOCIUS, 2015)
This classroom action research is motivated learning conditions IPS in SMP Negeri 3 Belawang particular class VIII A shows the very low interest in learning and learning outcomes that have not reached the minimum standard of thoroughness is 68. The exact cause is lack of teaching and learning strategies are applied, thus requiring their approach and a suitable method in learning. The hypothesis in this study is action If implemented cooperative learning model tife Scrambel, then the interest and student learning outcomes VIIIA class in SMPN 3 Belawang will increase. The method used in this research is a classroom action research method, commonly known by the term Classroom Action Research, which is a scrutiny of the learning activities in the form of an action, which is deliberately raised and occur within a class together. Based on the first cycle there is an increase in total score of 2.00 out of a score of 75.57 into a 77.57 score in spite of the increase in the average score of the class in the first cycle small however, can be overcome with improved learning outcomes in the second cycle is counted from 75.21 into 80.15 as well as the classical completeness also increased from post test cycle 1 at 78.57 percent and the post test cycle 2 at 82.14 percent.Keywords: Interest, Learning Outcomes, IPS, Model Scrambel